The potential of Empty Fruit Bunch (EFB) biochar produced from Modification of Gas Burner (MGB) as a soil amendment at different temperature level as compared to Top Lid Updraft (TLUD) and muffle furnace heating / Syed Ahmad Ibrahim Al-Kired S. Hasan - S. Hasan, Syed Ahmad Ibrahim Al-Kired (Faculty of Plantation and Agrotechnology, 2018)
Top-Lid Updraft (TLUD) stove and muffle furnace heating is one of the methods to produce biochar trough slow pyrolysis process. However, there is a limitation involve the TLUD stove and muffle furnace heating which are poorly designed may result in high gas emission and more costing in term of operation and maintenance respectively. The new method of slow pyrolysis to produce biochar which is “Modification of Gas Burner (MGB)” has innovated to overcome the problem. The purposes of this study were to investigate the physco-chemical properties of Empty Fruit Bunch (EFB) biochar produce from MGB at three different temperatures and to compare their properties with TLUD stove and muffle furnace heating. Sample of EFB used in this study was collected from Serting Hillir Oil Palm Mill, Negeri Sembilan, Malaysia. Biochar from dried EFB was produce from MGB at three different range of temperature and different type of slow pyrolysis process (MGB, TLUD stove and muffle furnace). The experiment outcome show the increasing temperature of biochar produced from MGB will increase the total ash, pH and EC value of the biochar. For the three different type of pyrolysis process, the results showed that biochar produce form MGB, TLUD stove and muffle furnace heating has high in pH ranging from 9.1 to 10.4. Between these three method , TLUD stove has a lower ash content, pH and EC value, phosphorus and potassium compared to MGB400 and muffle furnace heating. It is was found that EFB biochar that produced from MGB400 which is compatible with muffle furnace in term of physical and chemical properties has a potential as a new soil amendment with low cost of production.